Climate Change Challenge 26th Conference of Parties (COP26) climate summit is crucial but may be disappointing? - K Suresh (Global Journal of Ecology - Peertechz Publications, 2021)
Human activity is the main cause of climate change. People burn fossil fuels and convert land from forests to agriculture. Burning fossil fuels produces carbon dioxide, a greenhouse gas. Climate change due to vehicular movements, industries, and deforestation for creating newer inhabitations affects the environmental and social determinants of health. An effective public health response to climate change is involves preventing injuries and illnesses, escalating public health preparedness, and reducing risk of consequences of all listed climate change immediate support, manage health effects and outbreaks. The world leaders are gathering in Glasgow for COP26, today the October 31st, 2021, to carry forwards the unfinished agenda. The process is ruled by arriving at consensus, and the pace is set by the least willing countries. In 2019, developed countries provided $16.7 billion as a grant, that amounts to just $1 per month for climate finance. Developed countries can surely afford more than this. A credible climate finance plan from them is, therefore, crucial. The world's 20 biggest economies recently endorsed a landmark deal on a global minimum corporate tax rate of 15% and will aim to implement the rules by 2023 for climate financing.  The main reason why cop26 process matters is that the science, diplomacy, activism, and public opinion that support it make up the best mechanism the world currently must help it come to terms with a fundamental truth. Looking at the progress made since the imitation of COP so far and minimal groundwork that has been done to achieve them, most of the demands may not be met.  India's ambitious 450 GW renewable energy goal by 2030, its hydrogen mission, plan to move Indian railways to 'net-zero' emission by 2030, land degradation neutrality and massive programme to increase forest cover- natural carbon sink the key points the country will commit to drive home.  Forty-five nations pledged to step up protection of nature and overhaul farming to cut greenhouse gas emissions, but major economies led by the US, Japan and Germany and developing nations such as India, Indonesia, Morocco, Vietnam, Philippines, Gabon, Ethiopia, Ghana, and Uruguay backed from commitments. The steps include leveraging over $4 billion of new public sector investment into agricultural innovation, including the development of climate-resilient crops and regenerative solutions to improve soil health. I think climate challenges will be met, not because of summits and global idealism but because of enormous sums likely to be spent on green innovation by profit-driven corporations, incentivised by modest government subsidies and mandates Material & methods: This article is a review of available literature on Impact of climate change on health and global Climate change efforts, in press and various government and UN agency documents.